2020
DOI: 10.21037/tlcr-20-523
|View full text |Cite
|
Sign up to set email alerts
|

Is clinical target volume necessary?—a failure pattern analysis in patients with locally advanced non-small cell lung cancer treated with concurrent chemoradiotherapy using intensity-modulated radiotherapy technique

Abstract: Background: Our previous dosimetric study showed that for locally advanced non-small cell lung cancer (LA-NSCLC), radiotherapy with intensity-modulated radiotherapy (IMRT) technique could deliver sufficient dose coverage to subclinical regions and reduce the dose to normal tissues with the omission of clinical target volume (CTV). To further clinically validate this strategy, we conducted the current study to analyze the failure pattern for patients with LA-NSCLC treated with concurrent chemotherapy and CTVomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Further studies are needed to find the most immunogenic SABR doses to be used in combination with immunotherapy. Modern radiation modalities have created conditions to reduce the dose of organs at risk (OARs), to adaptively replan, to reduce the PTV, and to perform CTV-omitted RT, and elective nodal RT [ 91 , 145 , 146 ]. The safety and efficacy of CTV-omitted RT and elective nodal RT merits future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to find the most immunogenic SABR doses to be used in combination with immunotherapy. Modern radiation modalities have created conditions to reduce the dose of organs at risk (OARs), to adaptively replan, to reduce the PTV, and to perform CTV-omitted RT, and elective nodal RT [ 91 , 145 , 146 ]. The safety and efficacy of CTV-omitted RT and elective nodal RT merits future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that irradiation of the mediastinal lymph nodes may lead to lymphopenia, which could further lower immunity and affect prognosis. 16,17 Therefore, we speculated that a high dose of postoperative radiotherapy might lead to more toxicities and lower immunity, and these factors may have contributed to the poor prognosis of the high-dose group.…”
Section: Discussionmentioning
confidence: 99%
“…The specific implementation process of radiotherapy plan, dose requirements for treatment planning, and radiation techniques are described elsewhere. 26 Definitive CRT was defined as two or more cycles of platinum‐based chemotherapy concurrently or sequentially with curative thoracic radiotherapy (54–66 Gy), wherein the mean dose to the lung was <20 Gy, V20 (the volume of the lung parenchyma that received 20 Gy or more) was <35%, or both. Patients receiving corresponding TKIs in addition to definitive CRT, before disease recurrence, were allowed and those receiving durvalumab consolidation were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with pathologically confirmed NSCLC, determined to be inoperable with locally advanced NSCLC generally through multidisciplinary discussions, treated with definitive CRT, and had their tumor tissue tested for the status of common driver genes (including EGFR, ALK, and ROS1) at the Department of Pathology of the Fudan University Shanghai Cancer Center from January 2013 to March 2021 were retrospectively enrolled. The specific implementation process of radiotherapy plan, dose requirements for treatment planning, and radiation techniques are described elsewhere 26 . Definitive CRT was defined as two or more cycles of platinum‐based chemotherapy concurrently or sequentially with curative thoracic radiotherapy (54–66 Gy), wherein the mean dose to the lung was <20 Gy, V20 (the volume of the lung parenchyma that received 20 Gy or more) was <35%, or both.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation